Final Evolution and Delayed Explosions of Spinning White Dwarfs in Single Degenerate Models for Type Ia Supernovae - Benvenuto, Omar Gustavo (2015)
We study the occurrence of delayed SNe Ia in the single degenerate scenario. We assume that a massive carbon– oxygen (CO) white dwarf (WD) accretes matter coming from a companion star, making it spin at the critical rate. We assume uniform rotation due to magnetic field coupling. The carbon ignition mass for non-rotating WDs is M_{ig}^NR 1.38≈M_{⨀}, while for the case of uniformly rotating WDs it is a few percent larger (M_{ig}^R 1.43≈M_{⨀}). When accretion rate decreases, the WD begins to lose angular momentum, shrinks, and spins up; however, it does not overflow its critical rotation rate, avoiding mass shedding. Thus, angular momentum losses can lead the CO WD interior to compression and carbon ignition, which would induce an SN Ia. The delay, largely due to the angular momentum losses timescale, may be large enough to allow the companion star to evolve to a He WD, becoming undetectable at the moment of explosion. This scenario supports the occurrence of delayed SNe Ia if the final CO WD mass is 1.38M_{⨀} < M < 1.43 M_{⨀}. We also find that if the delay is longer than ∼3 Gyr, the WD would become too cold to explode, rather undergoing collapse.